2006
DOI: 10.1007/s00787-006-0526-7
|View full text |Cite
|
Sign up to set email alerts
|

Current comorbidity among consecutive adolescent psychiatric outpatients with DSM-IV mood disorders

Abstract: Adolescent depression presents with age- and sex-dependent patterns of multiple co-occurring problem areas. While many clinical characteristics of adolescent depression are not affected by comorbidity, comorbidity associates with increased impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
42
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 55 publications
2
42
0
1
Order By: Relevance
“…Only current diagnoses were included for the analyses presented in this article. Comorbidity between any disorder categories (e.g., mood disorder and anxiety disorder) or individual diagnoses (e.g., MDD and general anxiety disorder) and multiple comorbidity were assessed [Karlsson et al, 2006]. All the research diagnoses were confirmed in a diagnostic meeting.…”
Section: Diagnostic Interview and Definitions Of Diagnostic Groups Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Only current diagnoses were included for the analyses presented in this article. Comorbidity between any disorder categories (e.g., mood disorder and anxiety disorder) or individual diagnoses (e.g., MDD and general anxiety disorder) and multiple comorbidity were assessed [Karlsson et al, 2006]. All the research diagnoses were confirmed in a diagnostic meeting.…”
Section: Diagnostic Interview and Definitions Of Diagnostic Groups Anmentioning
confidence: 99%
“…DD was defined as preexisting DY with a duration of at least 1 year prior to the onset of a superimposed MDD. The category of minor depression comprised subjects with DSM-IV diagnoses of depression not otherwise specified (NOS; n 5 17) and adjustment disorder with depressed mood [n 5 2; Karlsson et al, 2006]. The diagnoses of Axis II disorders also followed DSM-IV guidelines, so that persistent and systematic pattern of behavior and emotional response had to be present prior to the onset of depressive episode [American Psychiatric Association, 1994].…”
Section: Diagnostic Interview and Definitions Of Diagnostic Groups Anmentioning
confidence: 99%
“…However, the mechanisms through which anxiety disorders impact psychosocial outcomes are unknown. Recent studies have documented similarity in psychosocial impairments experienced by adolescents with anxiety, MDD, and SUD (Angold et al 1999; Essau, 2003, 2008; Karlsson et al, 2006; Nottelmann and Jensen, 1999). Studies have also identified significant overlap in the risk factors for anxiety and MDD such as being female and stressful life events (Essau et al, 2000; Lewinsohn et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…First, depressive symptoms rarely occur in isolation. Over 70% of adolescents with a depressive disorder have an additional Axis I disorder (Karlsson et al, 2006), with depression showing pronounced co-occurrence with a broad range of clinical disorders and subthreshold symptoms (Essau, Conradt, & Petermann, 1999; Karlsson et al; Sanford, Szatmari, Spinner, & Munroe-Blum, 1995; Wittchen, Stein, & Kessler, 1999). Comorbidity might produce spurious associations between depression and romantic experiences, as their relation might be more precisely accounted for by symptoms of a co-occurring disorder.…”
mentioning
confidence: 99%